Study on the effectiveness of a community hypertension management model based on home smart blood pressure monitoring using IoT technology - Li, Cheng; Fan, Shuhao; Li, Hui (Frontiers in Public Health, 2024)
Background: Hypertension is rapidly increasing in China, but control rates are significantly low. There is a pressing need for effective management models in primary community health settings.Methods:In April 2023, 459 patients from six communities in Jinan City were enrolled using a multi-stage random sampling method and assigned to either a control group comprising 243 participants or an intervention group comprising 216 participants. The control group received standard hypertension care, whereas the intervention group participated in a novel IoT-based remote blood pressure monitoring program for six months. Data collection was conducted through detailed questionnaire surveys, cloud platform records, and community management records, both before and after the intervention period.The study employed difference-in-differences (DID) and mediation effect models to assess the effects of the IoT-based management model.Results: The DID model demonstrated that the intervention significantly reduced systolic blood pressure by 9.883 mm Hg and diastolic blood pressure by 6.553 mm Hg. The mediation effect model showed that the frequency of blood pressure measurement and attitudes and beliefs towards hypertension treatment had mediating effects, accounting for 5.82% and 8.07% of the total effect, respectively. The heterogeneity analysis revealed significant regional differences: rural residents experienced a greater decrease in systolic and diastolic blood pressures by 17.73 mm Hg and 7.002 mm Hg, respectively, compared to urban residents, whose diastolic pressure decreased by 5.950 mm Hg.Recommendations: It is advisable to develop differentiated hypertension management strategies tailored to specific regional needs to promote the deep integration and widespread application of smart blood pressure monitoring technology. Enhancing patient awareness and capabilities in managing their health condition is crucial for improving the blood pressure control level among community hypertension patients.